2020
DOI: 10.1021/acs.oprd.0c00483
|View full text |Cite
|
Sign up to set email alerts
|

Development and Proof of Concept for a Large-Scale Photoredox Additive-Free Minisci Reaction

Abstract: New route development activities toward ceralasertib (AZD6738) have resulted in the discovery of an efficient, acid additive-free, photoredox Minisci reaction. Mechanistic understanding resulting from LED-NMR reaction profiling, quantum yield measurements, and Stern−Volmer quenching studies have enabled optimization of the catalyst system, resulting in a significant enhancement in the rate of reaction. A large-scale continuous photoflow process has been developed, providing encouraging proofof-concept data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 42 publications
(60 reference statements)
0
56
0
Order By: Relevance
“…While the reaction had been optimized using laser-based reactor configurations, laser equipment was not available to Asymchem within the desired timeframe (1-2 months) so efforts were directed towards scaling the reaction using LEDs as the light source in conjunction with a plug flow reactor (PFR). [34][35][36][37] Asymchem had previous success scaling similar reactors using UV LEDs 10,11 and several different research groups have reported success using such reactions on scales up to 1 kg but greater scales were not known at the time but have been reported since. 34,37 After an LED-PFR system was selected, the focus became identifying stable feed solutions for the initial scale-up.…”
Section: Manuscriptmentioning
confidence: 99%
“…While the reaction had been optimized using laser-based reactor configurations, laser equipment was not available to Asymchem within the desired timeframe (1-2 months) so efforts were directed towards scaling the reaction using LEDs as the light source in conjunction with a plug flow reactor (PFR). [34][35][36][37] Asymchem had previous success scaling similar reactors using UV LEDs 10,11 and several different research groups have reported success using such reactions on scales up to 1 kg but greater scales were not known at the time but have been reported since. 34,37 After an LED-PFR system was selected, the focus became identifying stable feed solutions for the initial scale-up.…”
Section: Manuscriptmentioning
confidence: 99%
“…Longer term it would be beneficial to have a more convergent approach with a higher yielding route". 32 During the development of our sulfonimidoyl SNAr method, AZ's process team disclosed an improved route (Scheme 3A, middle left) 33 and an attempt at a photocatalyzed flow approach via a Minisci reaction (Scheme 3A, middle right) 34 . The newly developed process route to 1 (Scheme 3A, middle left) addressed the issue of installing a cyclopropyl methyl sulfide moiety from 129 and 130 in a single step, while still relying on an enantioselective enzymatic oxidation.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Longer term it would be beneficial to have a more convergent approach with a higher yielding route". 32 During the development of our sulfonimidoyl SNAr method, AZ's process team disclosed an improved route (Figure 5A, middle left) 33 and an attempt at a photocatalyzed flow approach via a Minisci reaction (Figure 5A, middle right) 34 . The newly developed process route to 1 (Figure 5A, middle left) addressed the issue of installing a cyclopropyl methyl sulfide moiety from 129 and 130 in a single step, while still relying on an enantioselective enzymatic oxidation.…”
Section: Synthetic Applicationsmentioning
confidence: 99%